PROGNOSTIC VALUE OF MOLECULAR MARKER ON OUTCOME IN PATIENTS WITH HIGH-GRADE GLIOMA. SINGLE INSTITUTIONAL EXPERIENCE - Stojkovski, Igor; Klisarovska, Violeta; Chakalaroski, Petar; Dzundeva, Jasmina; Ivanova, Maja; Petreska, Bojana (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University Skopje, R.N.Macedonia, 2020)
High-grade glioma (HGG) are among the most frequent primary brain tumors. Prognosis in HGG depends on histology, age, performance status, and other patient and tumor related factors. The 2016 revision of the WHO Classification of CNS Tumors introduced molecular characterization of HGG, with possible impact on prognosis. Analysis of a total of 49 patients with HGG with known MGMT methylation status and IDH1 and IDH2 mutation has been done. All patients undergo surgery, followed by concurrent chemoradiotherapy and adjuvant chemotherapy with temozolomide. Median follow up of all patients was 21,3 months (6,2-52,1 months). The Median Disease-free survival (DFS) was 20,3 months, and the median overall survival (OS) was calculated as 21,8 months. Patients has been stratified according to MGMT methylation status and IDH1 and IDH2 mutation status. DFS and OS have been compared between groups. The assessment shows 2-year DFS and OS were 45,5% and 54% for methylated and 40,4% and 47,8 for unmethylated patients. 2-year DFS and OS were 75% and 86% for IDH1 mutated patients and 34,12% and 47,1% for IDH1 unmutated patients. Two-year DFS and OS were 56% and 83% for IDH 2 mutated patients and 28,8% and 40,9% for IDH2 unmutated patients. There were suggestions for favorable prognostic factor for both MGMT methylation and IDH1 and IDH2 mutation, but we did not show any statistically significant difference of DFS and OS between MGMT methylated and unmethylated patients and between IDH1 and IDH2 mutated and unmutated patients due to small specimen and relatively short follow up.
Keywords: Chemoradiotherapy; Glioma; Molecular Characterization